2020
DOI: 10.1002/ajb2.1579
|View full text |Cite
|
Sign up to set email alerts
|

Genetic insights into the evolution of genera with the eastern Asia–eastern North America floristic disjunction: a transcriptomics analysis

Abstract: Premise Large disjunctions in species distributions provide excellent opportunities to study processes that shape biogeographic patterns. One such disjunction is the eastern Asia–eastern North America (EA‐ENA) floristic disjunction. For many genera with this disjunction, species richness is greater in EA than in ENA; this pattern has been attributed, in part, to higher rates of molecular evolution and speciation in EA. Longer branch lengths have been found in some EA clades, relative to their ENA sister clades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…With better data and methodologies available today, biogeographic studies of individual clades can provide a more accurate picture of their dynamic histories on range expansion and restriction and provide solid baseline data for understanding the origin of disjunctions and the assembly of the Earth's phytogeography. The origin of the floristic disjunction/floristic similarity between eastern Asia and North America has been of interest for the past three decades (e.g., Qian and Ricklefs, 2000; Xiang and Soltis, 2001; Donoghue and Smith, 2004; Ricklefs et al, 2004; Harris et al, 2013; Dong et al, 2019; Melton et al, 2020, 2022; see reviews by Wen, 1999; Wen et al, 2010, 2016). Clearly, detailed biogeographic studies of disjunct clades based on robust, dated, comprehensive phylogenies inferred from genome‐wide data using modern methodology are particularly valuable for evaluating hypotheses derived from previous meta‐analyses or synthesis (e.g., Donoghue and Smith, 2004; Wen et al, 2010) that were based on early methodology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With better data and methodologies available today, biogeographic studies of individual clades can provide a more accurate picture of their dynamic histories on range expansion and restriction and provide solid baseline data for understanding the origin of disjunctions and the assembly of the Earth's phytogeography. The origin of the floristic disjunction/floristic similarity between eastern Asia and North America has been of interest for the past three decades (e.g., Qian and Ricklefs, 2000; Xiang and Soltis, 2001; Donoghue and Smith, 2004; Ricklefs et al, 2004; Harris et al, 2013; Dong et al, 2019; Melton et al, 2020, 2022; see reviews by Wen, 1999; Wen et al, 2010, 2016). Clearly, detailed biogeographic studies of disjunct clades based on robust, dated, comprehensive phylogenies inferred from genome‐wide data using modern methodology are particularly valuable for evaluating hypotheses derived from previous meta‐analyses or synthesis (e.g., Donoghue and Smith, 2004; Wen et al, 2010) that were based on early methodology.…”
Section: Discussionmentioning
confidence: 99%
“…An updated classification is proposed using the PhyloCode with the hope to stabilize the names of this taxonomically highly controversial group. During the past two decades, the dogwood genus has become a model clade for bridging macro‐ and microevolution (Fan et al, 2004, 2007; Xiang et al, 2005, 2008; Xiang and Thomas, 2008; Zhang et al, 2008; Yu et al, 2017; Dong et al, 2019; Lindelof et al, 2020; Melton et al, 2020), for integrating phylogenetics, evolution, and developmental biology and molecular genetics (Feng et al 2009b, 2011, 2012, 2013; Liu et al, 2013; Zhang et al, 2013; Geng et al, 2016; Liu et al, 2016, 2017, 2019; Ma et al, 2017), and for integrating evolution with genetics, metabolomics, physiology, and/or ecology (Karlson et al, 2004; Sarnighausen et al, 2004; Call et al, 2016; Pais et al, 2017, 2018, 2020; Zhou 2021). Our study is also an important step facilitating further comparative studies, via a robust phylogeny that we provide as a framework for synthesizing different dimensions of dogwood biology that have been studied for many decades (e.g., Bate‐Smith et al, 1975; Eyde, 1988; Murrell, 1993, 1994; Xiang et al, 1993, 1998; Noshiro and Baas, 1998, 2000, and subsequent publications from the Xiang lab).…”
Section: Discussionmentioning
confidence: 99%
“…org] is an excellent source. When considering potentially applicable names, always take into account the geographic origin but consider known broad disjunctions, such as western North American vs. Central Asia (Weber 2003;Melton et al 2020) 5. If the degree of non-fittingness of the sample is deemed sufficient to consider a novelty and no applicable name appears to exist, the sample should be formally described.…”
Section: Conclusion: a Protocol For Consistent Alpha (And Gamma) Taxonomy In Lichen-forming Fungimentioning
confidence: 99%
“…Some have suggested that floristic regions in EA possess more complex habitats, larger spans of vegetational continuity, and more connections with tropical floristic elements than those in ENA ( Wen, 1999 ; Milne and Abbott, 2002 ). Moreover, a higher rate of molecular evolution in EA has been proposed to be tightly linked to the species diversity anomaly in the EA−ENA disjuncts ( Xiang et al., 2004 ), although recent work indicates that such a pattern does not hold for all disjunct genera ( Melton et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%